Integrating community knowledge into nature-based solutions for the sustainability of water ecosystem services: insight from local communities in Ecuador - Fonseca, Kalina; Espitia-Sarmiento, Edgar Fabian; Ilbay-Yupa, Mercy; Breuer, Lutz (Frontiers in Sustainability, 2024)
dimensions in a local community shape the adoption of specific nature-based solutions (NbS). This study provides crucial insights on NbS tailored to smallholder indigenous and peasant communities heavily reliant on water ecosystem services from headwater streams, lakes, ponds, and reservoirs in the páramo ecosystems of the central Ecuadorian Andes.Combining a multi-stakeholder workshop with bibliometric analysis, we developed a framework that integrates NbS aligned with local communities' PESTEL dimensions to sustain water ecosystem services. As a result, the lack of political will to sustain healthy aquatic ecosystems, urban-centred environmental investment, and agricultural expansion mainly influence the sustainability of water ecosystem services in the political, economic and environmental dimensions. Social, legal, and technological dimensions encompass community dissatisfaction, resistance to conservation, neglect of clean water and land use regulations, and limited innovation investment. Artificial floating islands and passive river restoration were the NbS adaptable to these PESTEL dimensions in our local communities.Artificial floating islands, a macrophyte-based technology that integrates community plant knowledge, are feasible even with limited financial resources. Passive river restoration complements them to promote headwater vegetation recovery and governance of water ecosystem services. Their integration supports drinking water supply, irrigation, fisheries, water purification, habitat conservation, soil formation carbon sequestration, and the achievement of several Sustainable Development Goals (SDGs) achievement. We provide decision-makers with a rigorous assessment of NbS for local communities communities, with the potential to scale to countries with similar contexts yet extendable to countries facing similar contexts and highlight the need for future research to explore NbS in regional or national frameworks. that tackles PESTEL challenges beyond local solutions.